PCR-Based Screening of Spinal Muscular Atrophy for Newborn Infants in Hyogo Prefecture, Japan - Noguchi, Yoriko (MDPI, 2022)
Spinal muscular atrophy (SMA) is a common devastating neuromuscular disorder, usually involving homozygous deletion of the SMN1 gene. Newly developed drugs can improve the motor functions of infants with SMA when treated in the early stage. To ensure early diagnosis, newborn screening for SMA (SMA-NBS) via PCR-based genetic testing with dried blood spots (DBSs) has been spreading throughout Japan. In Hyogo Prefecture, we performed a pilot study of SMA-NBS to assess newborn infants who underwent routine newborn metabolic screening between February 2021 and August 2022. Hyogo Prefecture has ~40,000 live births per year and the estimated incidence of SMA is 1 in 20,000–25,000 based on genetic testing of symptomatic patients with SMA. Here, we screened 8336 newborns and 12 screen-positive cases were detected by real-time PCR assay. Multiplex ligation-dependent probe amplification assay excluded ten false positives and identified two patients. These false positives might be related to the use of heparinized and/or diluted blood in the DBS sample. Both patients carried two copies of SMN2, one was asymptomatic and the other was symptomatic at the time of diagnosis. SMA-NBS enables us to prevent delayed diagnosis of SMA, even if it does not always allow treatment in the pre-symptomatic stage. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.